Uso do controle estatístico de processo (CEP) e análise de tempos: um estudo de caso em uma empresa do setor de confecções - Lisboa, Wenderlainy Patricia Macêdo (Universidade Federal Rural do Semi-Árido, 2020)
The present work aims to apply the Statistical Control of the Process (CEP) and the chronoanalysis to analyze the manufacturing process in a clothing company. Both tools are of great importance to the company, as they help control processes and assist in identifying bottlenecks. With this, it is possible to propose improvements for organizations to achieve their goals. In addition, the market is increasingly competitive, allowing the company to always seek excellence in its processes, which further increases the relevance of the proposed themes. To perform this research, the methodological procedure used was the application of cep and chronoanalysis in the process of manufacturing a pants in a company in the interior of Rio Grande do Norte, in order to optimize processes and increase production. Based on the results found, it was verified that it was possible to identify the existence of a bottleneck in production, based on the application of the chronoanalysis technique, and problems related to special causes affecting the variability of the manufacture of jeans, through the application of control graphics. Based on this, improvements were proposed for the company.
Monografia
Keywords: CEP; Cronoanálise; Qualidade; Mapeamento do processo; Confecções; ZIP code; Chronoanalysis; Quality; Process mapping; Defects; ENGENHARIAS::ENGENHARIA DE PRODUCAO